Enhancing Student Engagement and Writing in Language Education - Puncochar, Judith (JOMANTARA, 2025)
The topic of eliminating vague terms in student writing is used to exemplify three powerful instructionalmethods in language education: extensive instructor feedback, iterative draft writing, and student peer review. Together, these three teaching methods increase clarity of student writing and reduce the considerable time needed for effective instructor feedback. The instructor provided biweekly feedback on cumulative drafts written by each individual student. Instructor feedback drew student attention to vague pronouns with one-to-many representations (e.g., “this” and “that” [i.e., “ini” and “itu” in Bahasa Indonesia]). Students removed vague terms, edited sentences with more descriptive terms, and wrote a new section for their next draft. The process of instructor feedback and student editing and adding new writing was repeated throughout the semester. Near the end of the semester, students use their knowledge and writing skills in a structured peer review guided by a rubric. Ninety percent of students claimed removing vague terms was the most important writing strategy that they had learned during their academic careers. The three instructional methods of instructor feedback, student cumulative practice with writing, and student peer review apply to a variety ofsubjects, topics, and themes with a goal of improving student writing in language education.